2020
DOI: 10.52549/ijeei.v8i3.2268
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Low-Cost Wireless Bee-Hive Temperature and Sound Monitoring System

Abstract: Precision beekeeping requires data acquisition, data analysis, and applications where the initial phase-data acquired plays a key role. This method of apiculture could be used to measure different bee colony parameters in real time, leveraging on wireless sensing technologies, which aid monitoring of a bee colony, while preventing infectious diseases like colony collapse disordera major loss in the management of honey bee population. In this paper, a lowcost wireless technology-based system, which measures in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…However, despite research on these methods, sound processing seems to dominate in the detection of many harmful events in apiaries, such as swarming, external attacks, or even CCD (Table 1, C1, C3, C6 cases). As a result, researchers trying to detect these events have focused on creating IoT devices that collect sound data [17][18][19].…”
Section: Related Workmentioning
confidence: 99%
“…However, despite research on these methods, sound processing seems to dominate in the detection of many harmful events in apiaries, such as swarming, external attacks, or even CCD (Table 1, C1, C3, C6 cases). As a result, researchers trying to detect these events have focused on creating IoT devices that collect sound data [17][18][19].…”
Section: Related Workmentioning
confidence: 99%
“…To this end, the acoustic monitoring of beehives has emerged and is gaining popularity. In a recent literature review of beehive acoustics monitoring [24], several systems were reported showcasing tools for (i) bee activity detection [4,[25][26][27], (ii) beehive strength monitoring [28], (iii) queen absence detection [3,5,[29][30][31], (iv) swarming detection [22,23,[32][33][34], (v) pathogen or parasite infestation detection [35], (vi) detection of environmental pollutants and chemicals [36][37][38][39], and (vii) measuring of honeybee reaction to smoke [40], as well as overall beehive monitoring (e.g., identifying normal and abnormal hive, swarming duration, bee activity time) [41,42]. From a geographical perspective, most contributions have come from the USA, UK, Japan, Slovenia, and Italy.…”
Section: Introductionmentioning
confidence: 99%